The use of video to improve young learners' listening comprehension achievement - Aji, Aulia Adilla (2020)
This research is aimed to improve the young learners' listening comprehension achievement by using video at Eddy's English. According to the preliminary study by observing the young learners' ability of listening at Eddy's English, it was found that the young learners' had difficulties in understanding what the speaker said. It was known from the percentage of the young learners' previous listening comprehension achievement was 61.76%. Thus, the researcher conducted a classroom action research (CAR) to overcome the problem by using video to teach listening comprehension. In this research, the researcher collected the data from the results of the students' listening comprehension post-test and observation in the teaching and learning process of listening comprehension. It was found that the use of video improved the students' participation as well as the students' listening comprehension achievement at Eddy's English. Therefore, the researcher suggested the English teacher to use video to teach listening comprehension